Modified live vaccine strains of porcine reproductive and respiratory syndrome virus cause immune system dysregulation similar to wild strains - Stepanova, Katerina; Toman, Miroslav; Sinkorova, Jana; Sinkora, Simon; Pfeiferova, Sarka; Kupcova Skalnikova, Helena; Abuhajiar, Salim; Moutelikova, Romana; Salat, Jiri; Stepanova, Hana; Nechvatalova, Katerina; Leva, Lenka; et al. (Frontiers in Immunology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) emerged about 30 years ago and continues to cause major economic losses in the pork industry. The lack of effective modified live vaccines (MLV) allows the pandemic to continue. We have previously shown that wild strains of PRRSV affect the nascent T cell repertoire in the thymus, deplete T cell clones recognizing viral epitopes essential for neutralization, while triggering a chronic, robust, but ineffective antibody response. Therefore, we hypothesized that the current MLV are inappropriate because they cause similar damage and fail to prevent viral-induced dysregulation of adaptive immunity. We tested three MLV strains to demonstrate that all have a comparable negative effect on thymocytes in vitro. Further in vivo studies compared the development of T cells in the thymus, peripheral lymphocytes, and antibody production in young piglets. These three MLV strains were used in a mixture to determine whether at least some of them behave similarly to the wild virus type 1 or type 2. Both the This is a provisional file, not the final typeset article wild and MLV strains cause the same immune dysregulations. These include depletion of T-cell precursors, alteration of the TCR repertoire, necrobiosis at corticomedullary junctions, low body weight gain, decreased thymic cellularity, lack of virus-neutralizing antibodies, and production of non-neutralizing anti-PRRSV antibodies of different isotypes. These results may explain why the use of current MLV in young animals may be ineffective and why their use may be potentially dangerous. Therefore, alternative vaccines, such as subunit or mRNA vaccines or improved MLV, are needed to control the PRRSV pandemic.